Special Consideration for Intraosseous Arteriovenous Malformations - Do, Young Soo; Park, Kwang Bo (Seminars in Interventional Radiology, 2017)
Intraosseous arteriovenous malformations (AVMs) have been associated with distortion, hypertrophy, osteolytic skeletal changes, bleeding, leg length discrepancy, and pathologic fracture. Computed tomography or magnetic resonance imaging is helpful in the evaluation of the extent and depth of intraosseous AVMs and associated soft-tissue AVMs. Treatment approaches can differ, depending on the angiographic classification. Embolotherapy with ethanol, coils, or n-butyl cyanoacrylate is the primary treatment for symptomatic intraosseous AVMs, and the goal of treatment is symptom improvement with few complications.
Keywords: intraosseous AVM; embolization; embolotherapy; interventional radiology